Design and analysis of a new frame-foot wall-climbing robot. (June 2022) - Huo, Ping; Xu, Yangyang; Yu, Jiangtao; Wang, Yazhou
This paper designs and develops a new type of frame-foot wall-climbing robot structure. According to the bionic principle, a new parallel telescopic leg structure is proposed, and the 3D design of the overall structure of the wall-climbing robot is completed. Secondly, the kinematics analysis of the robot is carried out, and the forward and inverse solution models of the leg structure position are completed to verify the feasibility of the leg structure stability. Based on the polynomial motion equations, the robot motion planning and gait design are established, and the speed and acceleration change graphs of the leg structure slider are obtained, which avoids the rigid impact between the parts, and realizes the alternate adsorption and continuous movement of the robot legs, which the rationality of the legs structure design and the stability of the movement are verified. Through simulation and experimental results, it is shown that during the robot's movement, the leg structure can adjust the step distance and step height according to obstacles, so as to achieve the expected obstacle crossing goal. The leg structure is adjusted according to the working environment to ensure that the fuselage and the working surface are always kept parallel to improve the stability of the overall structure.